2017
DOI: 10.1590/1678-4324-2017160416
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia Coli: Characteristics of Carbapenem Resistance and Virulence Factors

Abstract: In this study, fifty Escherichia coli strains were analyzed by multiplex polymerase chain reaction for the genes expressed carbapenemase and virulence factors in order to determine the presence of carbapenemase and nine virulence factors and investigate the association between these two characteristics. When carbapenemase susceptibility was taken into consideration, OXA-48 type carbapenemase was determined for 22% of the total strains. Also, the frequency of virulence gene regions in E.coli infections and viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Among MDR E. coli, AMR caused by ESBL is mainly due to the bla CTX-M family, particularly bla CTX-M-15 and -14 , compared to the less frequently observed bla SHV and bla OXA families [6][7][8]. As per the literature, carbapenem resistance in E. coli is mostly mediated by bla OXA-48 [9], bla NDM and bla VIM genes [10]. Also, increasingly, resistance is being reported for fluoroquinolones and third-and fourth-generation cephalosporins and ST-131 predominates globally among such MDR E. coli strains [11].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Among MDR E. coli, AMR caused by ESBL is mainly due to the bla CTX-M family, particularly bla CTX-M-15 and -14 , compared to the less frequently observed bla SHV and bla OXA families [6][7][8]. As per the literature, carbapenem resistance in E. coli is mostly mediated by bla OXA-48 [9], bla NDM and bla VIM genes [10]. Also, increasingly, resistance is being reported for fluoroquinolones and third-and fourth-generation cephalosporins and ST-131 predominates globally among such MDR E. coli strains [11].…”
Section: Introductionmentioning
confidence: 79%
“…Globally, bla OXA-48 type were the most commonly reported carbapenemases among E. coli [21], followed by bla NDM [22], bla IMP [23] and bla KPC [24]. Studies have reported occurrence of bla OXA-48 from as low as 3% to 22% [25,9]. In contrast, a previous report from India on carbapenem-resistant clinical E. coli isolates from 2013 and 2015 has shown that bla NDM was common among carbapenemases in E. coli (70%), followed by bla OXA-48 (24%) and bla VIM (17%).…”
Section: Discussionmentioning
confidence: 99%
“…bla OXA-48 type carbapenemases are the most commonly reported in E. coli [19] followed by bla NDM [20], bla IMP [21] and bla KPC [22] type carbapenemases have also been determined. Studies report occurrence of bla OXA-48 from as low as 3% to 22% [23, 9]. A report from India has shown, bla NDM was common among carbapenemases in E. coli (70%), followed by bla OXA-48 (24%) and bla VIM (17%).…”
Section: Discussionmentioning
confidence: 99%
“…Among MDR E. coli , AMR mediated by ESBL is mainly due to the bla CTX-M family, particularly bla CTX-M-15 and 14, compared to the less frequent observation of bla SHV and bla OXA families [68]. Carbapenem resistance in E. coli was mostly reported to be mediated by bla OXA-48 [9], bla NDM and bla VIM [10]. Also, AMR among E. coli is increasingly reported for fluoroquinolones and third- and fourth-generation cephalosporins.…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli is one of the most common causative agents of a wide range of clinical infections varying from meningitis, urinary tract infections, and sepsis. [1] Carbapenems are the only antibiotic option left for the treatment of infections caused by multidrug-resistant E. coli . However, the emergence of carbapenem resistance leads to the failure of empirical therapy with carbapenems.…”
Section: Introductionmentioning
confidence: 99%